Degradation kinetics of sodium alginate via sono-Fenton, photo-Fenton and sono-photo-Fenton methods in the presence of TiO2 nanoparticles. (January 2017) - Zhou, Qingfeng; Liu, Yanfeng; Yu, Gaobo; He, Furui; Chen, Kai; Xiao, Dunchao; Zhao, Xinyu; Feng, Yuhong; Li, Jiacheng
Abstract: Sono-photo-Fenton, sono-Fenton and photo-Fenton methods combined with heterogeneous TiO2 nanoparticles are adopted to investigate the degradation of sodium alginate (NaAlg), and the kinetics mechanism is also explored. Experimental results suggest that the reaction order of NaAlg degradation ( n ) is 0.51 and the extent of photocatalytic degradation can increase with the loading of TiO2 nanoparticles. Meanwhile, as the catalyst concentration increases from 0.05 to 0.5 gL −1, the degradation rate constant ( k ) is decreased. In addition, the structure of degraded NaAlg is characterized by Fourier transform infrared (FT-IR), 1 H NMR spectroscopy, and X-ray diffraction analyses. The FT-IR and 1 H NMR spectra results indicate that the C2-C3 bond in the structure of NaAlg is broken and intra-molecular esters are formed during the degradation process due to the strong oxidization of the Fenton system. In general, the sono-photo-Fenton process with TiO2 nanoparticles could provide an efficient way to degrade the NaAlg to low-molecular-weight. Graphical abstract: Scheme of the hydroxyl radical production mechanism and it is the key factor for the degradation of NaAlg.